2013
DOI: 10.1371/journal.pone.0068171
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Induce Pre-Metastatic Osteolytic Disease and Help Bone Metastases Establishment in a Mouse Model of Metastatic Breast Cancer

Abstract: Bone metastases, present in 70% of patients with metastatic breast cancer, lead to skeletal disease, fractures and intense pain, which are all believed to be mediated by tumor cells. Engraftment of tumor cells is supposed to be preceded by changes in the target tissue to create a permissive microenvironment, the pre-metastatic niche, for the establishment of the metastatic foci. In bone metastatic niche, metastatic cells stimulate bone consumption resulting in the release of growth factors that feed the tumor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 46 publications
(58 reference statements)
1
83
1
1
Order By: Relevance
“…Tumour-specific CD4 + T cells are reported to induce pre-metastatic niches in the bone by secreting receptor activator of nuclear factor-κB ligand (RANKL) and thus increasing osteoclastogenesis, which promotes bone metastasis of breast cancer cells 49 . Interestingly, conditioned medium from 4T1 breast cancer cells increases the number of T Reg cells in the pre-metastatic lung by inducing CCL22 expression in the lung stroma 32 .…”
Section: Pre-metastatic Niche Formationmentioning
confidence: 99%
“…Tumour-specific CD4 + T cells are reported to induce pre-metastatic niches in the bone by secreting receptor activator of nuclear factor-κB ligand (RANKL) and thus increasing osteoclastogenesis, which promotes bone metastasis of breast cancer cells 49 . Interestingly, conditioned medium from 4T1 breast cancer cells increases the number of T Reg cells in the pre-metastatic lung by inducing CCL22 expression in the lung stroma 32 .…”
Section: Pre-metastatic Niche Formationmentioning
confidence: 99%
“…Zhang and colleagues found that stimulating a T-cell response in mice reduced tumor burden and inhibited overall tumor growth in bone [77]. T cells have also been implicated in secreting RANKL and inducing osteoclastogenesis, leading to bone destruction prior to tumor establishment in bone [78]. Together these finding suggest that T cells may have opposing roles in TIBD, one where they can decrease tumor growth in bone and the other being that they can stimulate bone destruction.…”
Section: Immune Cellsmentioning
confidence: 99%
“…59 Accordingly, more pro-osteoclastic cytokines (IL-1b, IL-6, IL-17F, RANKL, tumor necrosis factor (TNF)-a) but less osteoprotegerin (OPG), a decoy receptor for RANKL, are found in the serum obtained from 4T1-bearing animals. 59 Interestingly, production of these cytokines parallels what is seen during tumor dissemination.…”
Section: Lymphoid Cellsmentioning
confidence: 99%
“…59 Accordingly, more pro-osteoclastic cytokines (IL-1b, IL-6, IL-17F, RANKL, tumor necrosis factor (TNF)-a) but less osteoprotegerin (OPG), a decoy receptor for RANKL, are found in the serum obtained from 4T1-bearing animals. 59 Interestingly, production of these cytokines parallels what is seen during tumor dissemination. When CD3 þ T cells are isolated from 4T1-or 67NR-bearing mice and transplanted into nude mice, bone loss is observed only in recipients of T cells derived from 4T1-bearing donors, and this is reversed by inhibiting RANKL in 59 When 4T1 cells are implanted into control or RANKLknockdown T-cell-transplanted mice, 95% of lymph node metastases and 100% of bone metastases are eliminated in the RANKL-knockdown T-cell-transplanted mice.…”
Section: Lymphoid Cellsmentioning
confidence: 99%
See 1 more Smart Citation